Social Pension Scheme and Health Inequality: Evidence From China's New Rural Social Pension Scheme - Hui Yuan; Shuoqi Chen; Guochen Pan; Lingyun Zheng (Frontiers Media S.A., 2022)
Health equality is an essential component of social justice, and the social policies should be as conducive to promoting health equality as possible. Based on the data from China, this article uses the regression discontinuity design method and the technique of decomposition of concentration index to examine whether the social pension schemes can significantly reduce health inequality among the residents, and tries to compute the contribution rate of pension benefit in alleviating the health inequality. Our results show that the pension benefit can improve the health level of the rural subscribers, especially for the low-income population. Implement of New Rural Pension Scheme contributes to reducing the health inequality among the rural elderly with contribution rate of 39.32%. Our results contain important policy implications.